Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3390/ijms131115360
|View full text |Cite
|
Sign up to set email alerts
|

Eclipsed Acetaldehyde as a Precursor for Producing Vinyl Alcohol

Abstract: The MP2 and DFT/B3LYP methods at 6-311++G(d,p) and aug-cc-pdz basis sets have been used to probe the origin of relative stability preference for eclipsed acetaldehyde over its bisected counterpart. A relative energy stability range of 1.02 to 1.20 kcal/mol, in favor of the eclipsed conformer, was found and discussed. An NBO study at these chemistry levels complemented these findings and assigned the eclipsed acetaldehyde preference mainly to the vicinal antiperiplanar hyperconjugative interactions. The tautome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…20 Moorthy, Venugopalan and co-workers have explored the role of formyl C–H⋯O interactions in defining crystal packing through their work on the formyl C–H⋯O interactions in the crystal structures of coumarins and aromatic aldehydes. 21 Osman et al 22 reported the relative stability of the eclipsed and bisected acetaldehydes at the Møller–Plesset second order perturbation level of theory (MP2) employing aug-cc-pVDZ basis sets. The eclipsed conformer of acetaldehyde with a relative energy stability in the range of 4.26 to 5.01 kJ mol −1 was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…20 Moorthy, Venugopalan and co-workers have explored the role of formyl C–H⋯O interactions in defining crystal packing through their work on the formyl C–H⋯O interactions in the crystal structures of coumarins and aromatic aldehydes. 21 Osman et al 22 reported the relative stability of the eclipsed and bisected acetaldehydes at the Møller–Plesset second order perturbation level of theory (MP2) employing aug-cc-pVDZ basis sets. The eclipsed conformer of acetaldehyde with a relative energy stability in the range of 4.26 to 5.01 kJ mol −1 was obtained.…”
Section: Introductionmentioning
confidence: 99%